Ficha interactica y su incidencia en el aprendizaje de los estudiantes de 5to. EGB paralelo “D”, U.E. Emigdio Esparza Moreno del canton Babahoyo, período lectivo 2022-2023 - Cabeza Pareja, Ginger Denise (2023)
A problem was observed regarding the limited use of technological tools due to lack of economic resources, affecting the restrictions of comprehensive reading, in the meaningful learning of elementary subjects, the objective of the case study being to determine the incidence of interactive worksheets in the learning of 5th grade students. Parallel EGB “D”, U.E. Emigdio Esparza Moreno from the Babahoyo canton, 2022-2023 school year. There is evidence that interactive worksheet activities strengthen cognitive development in learning through the didactic strategy by developing interactive worksheets on technological platforms such as Liveworksheets. Interactive worksheets are a digital, printable tool, as a complementary resource in class, which can be filled out interactively, self-corrected and sent to the teacher, helping students to be active in meaningful learning. The quantitative approach measures and analyzes statistics, the research method is inductive-deductive, based on reasoning, describing the problem and drawing conclusions from the interactive sheets and their impact on learning. Consulting bibliographic citations and classroom observation, possible solutions would be: prioritizing dynamic reading through interactive cards, about the student's environment and context, for reflection with critical thinking, through short texts and striking images; interactive games; and, didactic strategies of underlining, crossword puzzles, word searches. It is concluded that the benefits of interactive worksheets for students are twofold: the acquisition of answers and construction of knowledge.